How 911 callers and call-takers impact police encounters with the public: The case of the Henry Louis Gates Jr. arrest - Gillooly, Jessica W. (Criminology & public policy, 2020)
Research The Henry Louis Gates Jr. arrest provides an illuminating case study to show how the omission of dispatch in police reform conversations limits our understanding of police officer action. Using conversation analysis, this article analyzes the 911 call and radio transmission from the Gates incident to dissect the function of the 911 call-taker, and their impact on policing in the field. This analysis shines light on a previously overlooked call-taker function—risk appraisal—and concretely shows how the call-taker played a pivotal role in escalating the caller's uncertainty and, thus, primed the responding officer for a more aggressive encounter. Policy Implications Through unpacking precisely how the call-taker appraised risk—namely through extraction, interpretation, and classification of caller information—this article provides a framework to evaluate call-taker actions. The findings suggest the need for training that instructs call-takers to assess risk in more sophisticated ways. Preserving uncertainty may reduce the overestimation or underestimation of incidents and improve future police encounters with the public.